The effect of age on the pressor response produced by common carotid artery occlusion in conscious rats. - Bedran-de-Castro, M. T. [UNESP]; Bedran-de-Castro, J. C. [UNESP] (My University, 1990)
The pressor responses to 60 s of common carotid artery occlusion were studied in conscious male rats of different ages. Compared to rats at the age of 2 months, the initial peak and the maintained response in 6- 12- and 18-month old rats were well preserved. In 1-month old rats, both components were significantly depressed but in 24-month old rats only the initial peak of the pressor response was markedly attenuated. These findings demonstrate that age is an important factor in the response to common carotid artery occlusion which is more marked for the initial peak than the maintained response.